Antipsychotic utilization, healthcare resource use and costs, and quality of care among fee-for-service Medicare beneficiaries with schizophrenia in the United States. (31st December 2023) - Li, Pengxiang; Benson, Carmela; Geng, Zhi; Seo, Sanghyuk; Patel, Charmi; Doshi, Jalpa A.
Abstract: Background: No research to date has examined antipsychotic (AP) use, healthcare resource use (HRU), costs, and quality of care among those with schizophrenia in the Medicare program despite it serving as the primary payer for half of individuals with schizophrenia in the US. Objectives: To provide national estimates and assess regional variation in AP treatment utilization, HRU, costs, and quality measures among Medicare beneficiaries with schizophrenia. Methods: Cross-sectional descriptive analysis of 100% Medicare claims data from 2019. The sample included all adult Medicare beneficiaries with continuous fee-for-service coverage and ≥1 inpatient and/or ≥2 outpatient claims with a diagnosis for schizophrenia in 2019. Summary statistics on AP use; HRU and cost; and quality measures were reported at the national, state, and county levels. Regional variation was measured using the coefficient of variation (CoV). Results: We identified 314, 888 beneficiaries with schizophrenia. About 91% used any AP; 20% used any long-acting injectable antipsychotic (LAI); and 14% used atypical LAIs. About 28% of beneficiaries had ≥1 hospitalization and 47% had ≥1 emergency room (ER) visits, the vast majority of which were related to mental health (MH). Total annual all-cause, MH, and schizophrenia-related costs were $23, 662, $15, 000 and $12, 109, respectively. Among those with hospitalizations, 18.4% and 27.3% had readmission within 7 and 30 days and 56% and 67% had a physician visit and AP fill within 30 days post-discharge, respectively. Overall, 81% of beneficiaries were deemed adherent to their AP medications. Larger interstate variations were observed in LAI use than AP use (CoV: 0.21 vs 0.02). County-level variations were larger than state-level variations for all measures. Conclusions: In this first study examining a national sample of Medicare beneficiaries with schizophrenia, we found low utilization rates of LAIs and high levels of hospital admissions/readmissions and ER visits. State and county-level variations were also found in these measures.